Is Healthcare Information Technology Based on Evidence? - Koppel, R. (Yearbook of Medical Informatics, 2013)
Is healthcare information technology (HIT) based on evidence of efficacy? Are the trillions of dollars already devoted and in the pipeline for HIT implementations based on systematic evaluations? If evaluated, would those evaluations focus on patient safety, return on investment, clinical efficiency, improved clinician satisfaction, and/or workflow integration? Do we have reliable evidence of usable interfaces, of successful implementations, of data standards allowing interoperability, of continuous improvement, of responsiveness to clinician feedback?While measurement of HIT's efficacy is extraordinarily difficult—complicated by a myriad of other factors involved in providing healthcare and in organizational dynamics—it is not impossible. But is such evidence required before most implementations? Any implementation? Or are the goals of patient safety and efficiency so self-evident, profoundly desired, and laudable that HIT's beneficence is accepted without rigorous data? Note that lack of systematic evidence does not mean HIT is ineffective. HIT may provide untold benefits even if there is no hard proof of those benefits.We find that HIT is seldom objectively measured, and that evidence of its efficacy is at best spotty, and often influenced by self-promotion. Most measures, especially those associated with cost-benefit analyses, are aspirational or hubris transubstantiated into numbers.
Keywords: Healthcare IT; EHR; EMR; evidence-based; ROI; CPOE; HIT